Pendekatan Arsitektur Kontemporer Pada Perancangan Galeri Cokelat Pekanbaru - Tien Manurung; Yohannes Firzal; Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
As a result of processed product, chocolate has grown rapidly into a sculpture, clothes, hats and more. Market demands allow for more than chocolate products, but there is still minimal information dissemination about chocolate. Then it will be effective in chronologizing the chocolate products from initial knowledge, current production, to planning future production. Packaging all forms of knowledge about chocolate is more possible in the form of galleries. Chocolate Gallery is the place which is able to present the knowledge about the cultivation of Brown, as well as the results of the work of the chocolate itself. The Gallery is located in the city centre, is an assertion in its own to make an iconic building. The design uses the Contemporary Architecture approach that is authentic with the present nature, as well as the concept of the character of Cocoa's Skin. Key word: Gallery, Chocolate, Contemporary Architecture